The Role of the South Sumatra Provincial Government in Improving Teacher Professionalism - Arwan; Abdul Hadi; Ade Akhmad Saputra; Abdul Waris (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
This study aims to analyze the role of the South Sumatra Provincial Government in enhancing teacher professionalism. A qualitative methodology was employed, utilizing interviews, observations and documentation for data collection. The data analysis process involved three stages: data reduction, data presentation and conclusion drawing and verification. The findings of the study indicate a strong commitment from the regional government to encourage teacher participation in the Teacher Professional Education Program (PPG), supported by scholarships from the South Sumatra Provincial Government. Participation numbers have shown a steady increase: 70 teachers in 2021, 70 teachers in 2022, 118 teachers in 2023, and an expected 144 teachers in 2024. Despite this progress, there remain 3,567 Islamic Education (PAI) teachers who have not participated in the PPG. The support provided by the South Sumatra Provincial Government to improve teacher welfare through the PPG is crucial for enhancing teaching skills. This support includes the adoption of innovative learning methods and models, as well as improvements in the welfare of teachers in Senior High Schools (SMA), Vocational High Schools (SMK), and Special Education Schools (SLB) within the province. In conclusion, the South Sumatra Provincial Government plays a significant role in promoting teacher professionalism through financial support and welfare improvements, although challenges remain in reaching all eligible teachers